MENGEMBANGKAN POTENSI GURU DAN CALON GURU UNTUK MEWUJUDKAN PENDIDIKAN KARAKTER YANG EFEKTIF - Haryati, Sri (PKn Progresif, 2012)
Character education requires that each person's performance in the school environment animated by the spirit of character education, to have an effective method for the cultivation of values??, has a priority value becomes the primary institutional vision. For that we need a clear understanding of the difference between character education, moral education, values ??education, religious education, and PKN. This understanding is essential to the practice in the field we can keep putting myself every moment in education as a synergy for the presence of character education in schools